2015
DOI: 10.1007/s00018-015-1900-8
|View full text |Cite
|
Sign up to set email alerts
|

When our genome is targeted by pathogenic bacteria

Abstract: Eukaryotic cells repair thousands of lesions arising in the genome at each cell cycle. The most hazardous damage is likely DNA doublestrand breaks (DSB) that cleave the double helix backbone. DSBs occur naturally during T-cell receptor and immunoglobulin gene recombination in lymphocytes. DSBs can also arise as a consequence of exogenous stresses (e.g. ionizing irradiation, chemotherapeutic drugs, viruses) or oxidative processes. An increasing number of studies have reported that infection with pathogenic bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 81 publications
0
2
0
2
Order By: Relevance
“…Many studies have reported that infection with pathogenic bacteria can alter the host genome, producing double-strand breaks (DSBs) and other DNA modifications; even after DNA repair, chromosomes can remain scarred and cause genomic instability during the next round of cell division. Escherichia coli genotoxin induces DNA DSBs [ 36 ], while Pseudomonas aeruginosa induces single-strand breaks, DSBs, and oxidative DNA damage that activate a variety of DNA repair pathways [ 37 ]. The functional connection between the innate immunity and the DNA damage response has been demonstrated by many studies: for instance, Enterococcus faecalis —a Gram-positive intestinal commensal bacterium that produces extracellular superoxide—can polarize macrophages to induce a bystander effect that results in DSBs, tetraploidy, and CIN in target cells and can cause inflammation and colorectal carcinoma in interleukin (IL)-10 knockout mice [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that infection with pathogenic bacteria can alter the host genome, producing double-strand breaks (DSBs) and other DNA modifications; even after DNA repair, chromosomes can remain scarred and cause genomic instability during the next round of cell division. Escherichia coli genotoxin induces DNA DSBs [ 36 ], while Pseudomonas aeruginosa induces single-strand breaks, DSBs, and oxidative DNA damage that activate a variety of DNA repair pathways [ 37 ]. The functional connection between the innate immunity and the DNA damage response has been demonstrated by many studies: for instance, Enterococcus faecalis —a Gram-positive intestinal commensal bacterium that produces extracellular superoxide—can polarize macrophages to induce a bystander effect that results in DSBs, tetraploidy, and CIN in target cells and can cause inflammation and colorectal carcinoma in interleukin (IL)-10 knockout mice [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation or inhibition of p53 could help Neisseria gonorrhoeae, Listeria monocytogenes, Shigella flexneri to survive and multiply in the host cytoplasm. 32) Nevertheless, the results from our study (including proliferation curve and morphologic study) indicated that mutated p53 of MDA-MB231 had no obvious effect on intracellular growth of L. pneumophila.…”
Section: Discussionmentioning
confidence: 57%
“…Завершая обзор, следует отметить, что приведенные сведения о генотоксических эффектах отдельных представителей микробиоты изложены нами в краткой форме, без детального описания известных или предполагаемых молекулярных механизмов действия бактериальных эффекторов на ДНК клеток организмахозяина. Более подробную информацию можно получить, ознакомившись с соответствующими обзорами, опубликованными за последнее время [11,65,[88][89][90]. Здесь мы хотим подчеркнуть, что с учетом длительной коэволюции микробиоты с высшими организмами влияние бактериальной инфекции на целостность генома хозяина не является неожиданным.…”
Section: заключениеunclassified